2007
DOI: 10.1016/j.ydbio.2007.02.045
|View full text |Cite
|
Sign up to set email alerts
|

XSip1 neuralizing activity involves the co-repressor CtBP and occurs through BMP dependent and independent mechanisms

Abstract: The DNA-binding transcription factor Smad-interacting protein-1 (Sip1) (also named Zfhx1b/ZEB2) plays essential roles in vertebrate embryogenesis. In Xenopus, XSip1 is essential at the gastrula stage for neural tissue formation, but the precise molecular mechanisms that underlie this process have not been fully identified yet. Here we show that XSip1 functions as a transcriptional repressor during neural induction. We observed that constitutive activation of BMP signaling prevents neural induction by XSip1 but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
49
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 64 publications
6
49
0
1
Order By: Relevance
“…This further emphasizes the importance of CtBP. Depleting CtBP levels in neuronal precursors in vivo abolished neurulation [74]. Interestingly, induction of the neuronal markers N-CAM (Neural Cell Adhesion Molecule) and NRP (Neuropilin 1) does not seem to depend on the CtBP domain of ZEB2, since deletion of the N-terminal domain could abolish upregulation of these genes.…”
Section: The Zeb Transcription Factors Are Part Of a Multimeric Protementioning
confidence: 98%
See 1 more Smart Citation
“…This further emphasizes the importance of CtBP. Depleting CtBP levels in neuronal precursors in vivo abolished neurulation [74]. Interestingly, induction of the neuronal markers N-CAM (Neural Cell Adhesion Molecule) and NRP (Neuropilin 1) does not seem to depend on the CtBP domain of ZEB2, since deletion of the N-terminal domain could abolish upregulation of these genes.…”
Section: The Zeb Transcription Factors Are Part Of a Multimeric Protementioning
confidence: 98%
“…Additional experiments showed that ZEB2 functionality as a repressor depends on its deacetylase activity. Inhibition of HDAC by Trichostatin A treatment abrogated ZEB2-mediated neurulation in the Xenopus embryo [74]. Because both the NuRD complex and the cofactor CtBP have been shown to interact with HDAC, the cellular context selecting the proper deacetylase complex remains to be investigated.…”
Section: The Zeb Transcription Factors Are Part Of a Multimeric Protementioning
confidence: 99%
“…ZEB2 is a two-handed zinc-finger transcription factor and one of two members of the ZEB family in vertebrates; ZEB1 and -2 bind DNA at tandem, separated ) consensus E-box sites (Sekido et al, 1994) and may be in direct competition for E-protein-binding sites. ZEB2 can also mediate transcriptional repression via cooperation with activated Smads or through recruitment of the corepressor CtBP as well as histone deacetylase complexes, particularly NuRD (Verschueren et al, 1999;Postigo and Dean, 1999b;van Grunsven et al, 2007;Verstappen et al, 2008).The role of ZEB proteins in mature T cell function has not previously been investigated. However, Goossens et al (2015) recently found that ZEB2 drives immature T cell lymphoblastic leukemia in humans and mice, and in the mouse model this is caused by enhanced leukemia initiation potential and induction of CD127 expression.…”
mentioning
confidence: 99%
“…ZEB2 is a two-handed zinc-finger transcription factor and one of two members of the ZEB family in vertebrates; ZEB1 and -2 bind DNA at tandem, separated ) consensus E-box sites (Sekido et al, 1994) and may be in direct competition for E-protein-binding sites. ZEB2 can also mediate transcriptional repression via cooperation with activated Smads or through recruitment of the corepressor CtBP as well as histone deacetylase complexes, particularly NuRD (Verschueren et al, 1999;Postigo and Dean, 1999b;van Grunsven et al, 2007;Verstappen et al, 2008).…”
mentioning
confidence: 99%
“…Each Zn-finger cluster independently can bind a 5'-CACCT(G)-3' sequence located in the target promotor region . The domains outside the Zn-finger clusters seem less conserved and may be essential for the recruitment of various co-repressors, like CtBP (Grooteclaes & Frisch, 2000;Postigo & Dean, 1999b;van Grunsven et al, 2007) or co-activators like p300 or P/CAF (van Grunsven et al, 2006). Still a lot of controversy exists over whether Zeb proteins can only act as transcriptional repressors or as well as activators.…”
Section: Emt Regulators Of the Zeb Familymentioning
confidence: 99%